The Arcminute Microkelvin Imager - Consortium, AMI; Zwart, J; Barker, R; Biddulph, P; Bly, D; Boysen, R; Brown, A; Clementson, C; Crofts, M; Culverhouse, T; Czeres, J; Dace, R; et al. (2008)
The Arcminute Microkelvin Imager is a pair of interferometer arrays operating with six frequency channels spanning 13.9-18.2 GHz, with very high sensitivity to angular scales 30''-10'. The telescope is aimed principally at Sunyaev-Zel'dovich imaging of clusters of galaxies. We discuss the design of the telescope and describe and explain its electronic and mechanical systems.